2015
DOI: 10.1007/s00227-015-2630-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary shifts in the juvenile sea urchin Strongylocentrotus intermedius associated with the development of digestive enzymes

Abstract: ingested diets were observed for urchins >3 mm in TD. Our results suggest that the primary nutrient source of S. intermedius shifts from microalgae to macroalgae at ≈6 mm TD, and that macroalgae digestion efficiency in urchins ≥3 mm TD gradually improves because of activation of the enzymes. Highly activated enzymes enable sea urchins to efficiently digest nutrients stored in the bodies of macroalgae, allowing the primary nutrient source of S. intermedius to shift from microalgae to macroalgae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…From the results in this experiment, we found that an interregulatory relationship existed between TRPA1 and 5-HT in the gut of S. intermedius. Amylase and pepsin as representative digestive enzymes of sea urchins and their activities have been extensively used to evaluate the food digestion and absorption of sea urchins [15,16]. To investigate whether a correlation exists between digestive enzyme (amylase and pepsin) activities and the reciprocal regulation of TRPA1 and 5-HT in the gut of S. intermedius, we conducted a set of cascading experiments.…”
Section: Experiments 3: Digestive Enzyme Activities Are Negatively Co...mentioning
confidence: 99%
See 3 more Smart Citations
“…From the results in this experiment, we found that an interregulatory relationship existed between TRPA1 and 5-HT in the gut of S. intermedius. Amylase and pepsin as representative digestive enzymes of sea urchins and their activities have been extensively used to evaluate the food digestion and absorption of sea urchins [15,16]. To investigate whether a correlation exists between digestive enzyme (amylase and pepsin) activities and the reciprocal regulation of TRPA1 and 5-HT in the gut of S. intermedius, we conducted a set of cascading experiments.…”
Section: Experiments 3: Digestive Enzyme Activities Are Negatively Co...mentioning
confidence: 99%
“…The absorption and utilization of nutrients by S. intermedius are directly affected by digestive enzymes activities [15,16]. In this experiment, we used pepsin and amylase enzymes activities as two representative indicators to evaluate digestive and absorptive capacities of sea urchins.…”
Section: Digestive Enzyme Activities Are Negatively Correlated With T...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, sea urchins have a complex life history from larval to adult. They feed on floating microalgae during the planktonic larval phase, and postsettlement juveniles feed on sessile microalgae (Onitsuka et al, 2015). Therefore, different stages may have different digestive enzymes, and these digestive enzymes will affect the digestion and absorption of food by sea urchins and then affect growth or death.…”
Section: Introductionmentioning
confidence: 99%